Complex Basal Conditions and Their Influence on Ice Flow at the Onset of the Northeast Greenland Ice Stream. Issue 3 (9th March 2021) - Franke, Steven; Jansen, Daniela; Beyer, Sebastian; Neckel, Niklas; Binder, Tobias; Paden, John; Eisen, Olaf
Abstract: The ice stream geometry and large ice surface velocities at the onset region of the Northeast Greenland Ice Stream (NEGIS) are not yet well reproduced by ice sheet models. The quantification of basal sliding and a parametrization of basal conditions remains a major gap. In this study, we assess the basal conditions of the onset region of the NEGIS in a systematic analysis of airborne ultra‐wideband radar data. We evaluate basal roughness and basal return echoes in the context of the current ice stream geometry and ice surface velocity. We observe a change from a smooth to a rougher bed where the ice stream widens, and a distinct roughness anisotropy, indicating a preferred orientation of subglacial structures. In the upstream region, the excess ice mass flux through the shear margins is evacuated by ice flow acceleration and along‐flow stretching of the ice. At the downstream part, the generally rougher bed topography correlates with a decrease in flow acceleration and lateral variations in ice surface velocity. Together with basal water routing pathways, this hints to two different zones in this part of the NEGIS: the upstream region collecting water, with a reduced basal traction, and downstream, where the ice stream is slowing down and is widening on a rougher bed, with a distribution of basal water toward the shear margins. Our findings support the hypothesis that the NEGIS is strongly interconnected to the subglacial water system in its onset region, but also to the subglacial substrate and morphology. Plain Language Summary: The Northeast Greenland Ice Stream (NEGIS) transports a large amount of ice mass from the interior of the Greenland Ice Sheet (GrIS) toward the ocean. The extent and geometry of the NEGIS are difficult to reproduce in current ice sheet models because many boundary conditions, such as the properties of the ice base, are not well known. In this study, we present new characteristics of the ice base from the onset region of the NEGIS derived by airborne radio‐echo sounding data. Our data yield a smooth and increasingly lubricated bed in the upstream part of our survey area, which enables the ice to accelerate. Our results confirm the hypothesis that the position of the ice stream boundaries are coupled to the subglacial hydrology system. Key Points: Basal roughness at the onset of the NEGIS hints to a geomorphic anisotropy and a change in the geomorphological regime Basal water is funneled into the ice stream upstream and redistributed toward the shear margins further downstream A smooth and progressively lubricated bed reduces basal traction and favors the acceleration of the NEGIS at its onset